Differences in visio-spatial expertise between 1st division rugby players and non-athletes - Millard, L.; Shaw, I.; Breukelman, G. J.; Shaw, B. S. (Heliyon, 2021)
The present study aimed to compare the visual expertise of non-athletes (n = 40; 19-35 years old; age: 22.13 ± 2.37 years) to amateur, non-professional South-African Rugby Union (SARU) first-division club rugby players (n = 40; 19-35 years old; age: 23.88 ± 4.36 years; training age mean: 9.0 ± 1.5 years). Research suggests that athletes have enhanced visio-spatial expertise in comparison to non-athletes. However, conflicting research suggests that this is not always the case as non-athletes possess similar visio-spatial expertise in certain visual skills. Participants underwent an optometric assessment after which the following 6 visio-spatial intelligence (VSI) components were measured; accommodation facility, saccadic eye movement, speed of recognition, peripheral awareness, visual memory and hand-eye coordination using the following tests; hart near far rock, saccadic eye movement, evasion, accumulator, flash memory and ball wall toss tests. Results indicated that first-division rugby players performed significantly better (p = 0.05) in five of the six tests performed, except for visual memory (p = 0.893). While this study substantiates the notion that athletes, in this case first-division rugby players, performs significantly better in most VSI components, this is not the case for all, as with visual memory in this study. To more accurately distinguish between athletes and non-athletes, research should move away from tests that focus on basic visual function and develop sport specific testing methods that can be used by a variety of sports.